Energy requirements and efficiency of energy utilization in growing dairy goats of different sexes - Souza, A. P. [UNESP]; St-Pierre, N. R.; Fernandes, M. H. M. R. [UNESP]; Almeida, A. K. [UNESP]; Vargas, J. A. C. [UNESP]; Resende, K. T. [UNESP]; Teixeira, I. A. M. A. [UNESP] (Elsevier B.V., 2020)
The aim of this study was to investigate the effects of sex on the requirements for maintenance and efficiency of energy utilization in growing Saanen goats. A database from 7 comparative slaughter studies that included 238 Saanen goats was gathered to provide information for the development of prediction equations of energy requirements for maintenance and efficiency of energy utilization. The experimental design provided different levels of metabolizable energy intake (MEI) and empty body weight (EBW). The data were analyzed so that sex (e.g., intact males, castrated males, and females; n = 98, 80, and 60, respectively) was a fixed effect, and blocks nested in the studies and goat sex were random effects. For the development of linear and nonlinear equations, we used the MIXED and NLMIXED procedures in SAS (SAS Institute Inc., Cary, NC). Nonlinear regression equations were developed to predict heat production (HP, kcal/kg(0.75) of EBW; dependent variable) from MEI (kcal/kg(0.75) of EBW; independent variable). Using the comparative slaughter technique, the net energy requirement for maintenance (NEM) was calculated as the value of HP at MEI equal to zero. Additionally, NEM was evaluated based on the degree of maturity. The metabolizable energy requirement for maintenance was calculated as the value at which HP is equal to MEI. Efficiency of ME utilization for maintenance (k(m)) was calculated as the ratio between NEM and the metabolizable energy requirement for maintenance. Efficiency of energy utilization for growth (k(g)) was assumed to be the slope of the linear regression of retained energy (RE) on MEI above the maintenance stage (model intercept equal to 0). Efficiencies of RE as protein (k(p)) and as fat (k(f)) were calculated using the multiple linear regression of MEI above the maintenance (model intercept equal to 0) on RE as protein and as fat, respectively. Sex affected NEm (75.0 +/- 1.76 kcal/kg(0.)(75) of EBW for males and 63.6 +/- 2.89 kcal/kg(0.75) of EBW for females) and sex did not affect k(m) (0.63). In contrast, sex no longer affected NEM when degree of maturity was considered on its estimation. The k(g) was different between sexes (0.31 for castrated males and females, and 0.26 for intact males), but k(p) (0.21) and k(f) (0.80) were similar between sexes. These results may be useful for improving robustness of the energy requirement recommendations for dairy goats.
Keywords: comparative slaughter; degree of maturity; metabolizable energy; partitioning of energy